2017
DOI: 10.5430/jms.v8n3p51
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Glass Ceiling Effect for Women in Tourism and Hospitality

Abstract: The aim of this research is to explore the degree to which women face various barriers that prevent them as a worker in the tourism sector, in the city of Aqaba located in Jordan, from obtaining upper-level positions. These include internal business structural barriers, societal barriers, governmental barriers, situational barriers, and personal barriers. A total of 200 questionnaire containing 27 items was used to collect information from women who are working in the industries of tourism and hospitality. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
(23 reference statements)
1
5
0
6
Order By: Relevance
“…On the other hand, Table 5 and Table 6 indicate no significant difference among the individual, organizational and cultural factors that prevent employees from obtaining upper-level positions due to the moderator variable of age (Table 5) and work experience (Table 6). The obtained results are similar to the findings of Bazazo et al [40] on their research on the Jordanian tourism sector, indicating that several barriers among which: personal, internal business structural and societal barriers hinder the women's way to the top. However, they found statistical difference among the barriers women face that prevent them from obtaining upperlevel positions due to age, educational level, career level, and work experience, as well.…”
Section: Data Analysis and Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, Table 5 and Table 6 indicate no significant difference among the individual, organizational and cultural factors that prevent employees from obtaining upper-level positions due to the moderator variable of age (Table 5) and work experience (Table 6). The obtained results are similar to the findings of Bazazo et al [40] on their research on the Jordanian tourism sector, indicating that several barriers among which: personal, internal business structural and societal barriers hinder the women's way to the top. However, they found statistical difference among the barriers women face that prevent them from obtaining upperlevel positions due to age, educational level, career level, and work experience, as well.…”
Section: Data Analysis and Resultssupporting
confidence: 90%
“…Out of the study conducted among 199 respondents in the public organizations in Iran, the authors concluded that cultural and social factors are the most influential in not appointing women in management or higher positions in an organization [39]. Although to different extent, internal business structural barriers, societal barriers, governmental barriers, situational barriers, and personal barriers prevent women in the tourism sector in Jordan, from obtaining upper-level positions [40]. From the sample consisted of 150 women executives in Sri Lanka, Bombuwela and De Alwis [41] examined a significant effect of the individual factors, organizational factors and cultural factors on women career development and significant effect of family factor on the glass ceiling, thus concluding that there are significant effects of the glass ceiling on women's career development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…No entanto, a gestão da diversidade não dizimou o racismo institucional e a barreira do "teto de vidro" (BENTO, 1995;YAP, KONRAD, 2009;VRAVEC, BAČIK, 2012;COOK, GLASS, 2014;BAZAZO et al, 2017;MARRY, POCHIC, 2017;ARAÚJO, VASCONCELOS, 2018). Segundo Figueiredo (2008) e Coutinho et al (2009), os indicadores sociais reforçam que o ambiente do trabalho não está preparado para a diversidade.…”
Section: Diversidade E Sua Gestão No Contexto Das Organizaçõesunclassified
“…The independent variables (GC) are Internal Business Structural Barriers, Societal Barriers, Government Barriers, Personal Barriers, Situational Barriers (Bazazo et al, 2017), as adapted by Clevenger and Singh (2013), and (Kiaye and Singh, 2013). At the same time, the current research considers five barriers that women face in their career development (WCD): Internal Business Structural Barriers, Societal Barriers, Governmental Barriers, Situational Barriers, and Personal Barriers.…”
Section: H1: Internal Business Structural Barriers Influence Women's mentioning
confidence: 99%